Strategies in Online Speaking Classroom in the Time of Covid-19: A Descriptive Study at Tertiary Level - Afriani, Zelvia Liska; Utami, Valisneria (ENGLISH FRANCA : Academic Journal of English Language and Education, 2021)
Recently, the Covid-19 pandemic has transformed teaching and learning into a virtual model, which demands teachers to find their best strategy. This study aims to analyze the strategies applied by teachers at the tertiary level in the time of Covid-19. The researchers employed a descriptive research design conducted in one of the Islamic universities at Bengkulu. The subjects were two English as a foreign language (EFL) teaching staff who taught speaking skills at the beginner level. The data was obtained through a semi-structured interview. The observation was also done during one semester, where the researchers took part in the online classrooms. After the data was collected, the researchers analyzed the data by following some steps: (1) data reduction, (2) data display, and (2) conclusion drawing/verification. The findings revealed that the English teachers used several teaching-speaking skills integrated with social media and mobile phone applications to be accessed easily. The strategies are lecturing, role-play, online group discussion, simulation, and drilling. They are blended with WhatsApp Group, Google Classroom, Zoom, and Instagram. Even though the learning process can be managed in this pandemic, face-to-face learning is still favorable.